Exploring Digital Communication: Language Use by South African University Students - Ndukwani, Tiyiselani; Muobeleheni, Shaun Livhuwani (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This study explores the use of language on social media. The researchers investigated the problems related to language that undergraduate students encounter when they socialize on cyber socializing platforms. The study also highlights the relationship between language and cyberbullying, incorporating AI tools used by cyber socializing platforms to explore their effectiveness in detecting improper linguistic communication on social media. The study employed a qualitative approach, which entailed semi-structured interviews to collect the desired data. Ten undergraduate students volunteered to be part of the interviews. The findings of this study showed that all 10 students encountered problems related to language, and for some students, these problems led to mental health issues. The following are some of the problems encountered by students when interacting on social media: slang, misinterpretation, grammar and spelling errors, informal language, fake news, language barriers, cyberbullying, discriminatory language, the difference between face-to-face communication and online communication, and AI tools such as natural language processing, having difficulties in detecting improper linguistic communication.